2018
DOI: 10.1007/s10389-018-0936-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal and child oral health and dental caries in Korea

Abstract: Aim The aim of this study was to examine the oral health-related behaviors in mothers and their children and the prevalence of dental caries in both. Subject and methods A sample of 2536 children and their mothers was selected from the Fifth Korean National Health and Nutrition Examination Survey. Variables were analyzed using multiple regression to evaluate the prevalence of dental caries among children and mothers, demographic socioeconomic status, and oral health-related behaviors.Results The average age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(20 reference statements)
1
8
1
10
Order By: Relevance
“…Higher income and educational attainment were associated with a higher probability of staying at home in this study. This is consistent with other studies that have found that behaviors related to improved health are associated with socioeconomic variables in adults and older adults [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Higher income and educational attainment were associated with a higher probability of staying at home in this study. This is consistent with other studies that have found that behaviors related to improved health are associated with socioeconomic variables in adults and older adults [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Genetics and environmental factors interact to influence individual health patterns, especially among mothers with poor self-rated oral health whose children are more likely to grow up with poorer oral health (Shearer, Thomson, Broadbent, & Poulton, 2011). The higher the number of a mother's decayed, missing, or filled permanent teeth (DMFT score), the higher the children's DMFT score was for their permanent teeth (Lee, Kim, Lee, & Kim, 2019). Although DMFT tends to increase with the age of the child (Singleton, Day, Thomas, Schroth, Klejka, Lenaker, & Berner, 2019), parents also need to be educated on the role that cavities play beyond the consequences of decayed teeth of their children, which may include reduced nutritional deficiencies and unhealthy body weights (Lee & Vann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…De esta forma, inadecuadas prácticas de salud bucal en infantes estarían asociadas con mayor presencia de enfermedad, posiblemente relacionada con insuficiente educación en salud bucal, deficiencias en la autoeficacia de los cuidadores y determinantes de la salud general en relación con hábitos de cuidado. No obstante, la respuesta por parte de las madres y/cuidadores de la frecuencia de cepillado podría estar influenciada por comportamientos socialmente deseados y puede que no necesariamente coincida con la frecuencia real de cepillado de los niños 40 .…”
Section: Discussionunclassified